Molecular Characterization of the GBA Gene in Patients from Southwest of Colombia with Gaucher Disease - Terranova,Daniela Arturo (2021)
Abstract Introduction Gaucher's disease (GD) is an autosomal-recessive lysosomal storage disorder that results from hereditary deficiency of the acid glucocerebrosidase enzyme, encoded by the GBA gene necessary for the degradation of glucosylceramide. Objective molecularly characterize the variants found in the GBA gene present in patients from the Southwest of Colombia with GD. Material and methods 19 patients were included in the study, clinically and enzymatically diagnosed with GD. A molecular analysis of the GBA gene was performed and the variants were subsequently searched in different population and clinical databases. A bioinformatic analysis was performed. Results The variants in the GBA gene reported were classified into: 14/19 homozygous patients, 4/19 compound heterozygote and 1/19 heterozygous. The presence of 7 variants coding for 8 different genotypes was reported. Also the known mutations like Asn409Ser, p.Leu483Pro, p.Lys237Glu, p.Glu427Lys, and p.Arg535His were identified in these patients. The most frequent genotype was p. Asn409Ser / Asn409Ser (36%). All the variants presented a pathogenic clinical significance. Conclusion The given study will make it possible to understand the susceptibility to GD in the population. This can help maintain the health quotient of the population through premarital counseling and therefore minimize the burden of disease among the population.